STRATEGI KOMUNIKASI @MERAPI_UNCOVER DALAM MENINGKATKAN PERAN CITIZEN JOURNALISM DI MEDIA SOSIAL - Marshinta Indah Sari; Sa’idah, Zahrotus (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study examines the communication strategies employed by the social media account@merapi_uncover in enhancing the role of citizen journalism on platforms such as Instagram, TikTok,and X (Twitter). In the digital era, characterized by rapid advancements in information technology, socialmedia has become a primary source of information for the public. @merapi_uncover is known for itsfocus on local news, including traffic accidents, crime, disasters, and social issues in Yogyakarta and itssurroundings. This study adopts a qualitative descriptive approach to explore the underlying meanings ofthis phenomenon and provide an in-depth understanding of the communication strategies applied. Thekey strategies identified include unique content creation, the use of local language to build emotionalconnections, community empowerment through active participation, as well as speed and accuracy indelivering information. A strict verification process before publication ensures the validity of theinformation, reducing the risk of misinformation. Informal interactions with followers, the use of simplelanguage, and quick responses help foster a strong relationship with the community. This study alsohighlights challenges such as filtering relevant information and technical constraints like signaldisruptions. Through a commitment to accuracy and transparency, this account has built a reputation asa reliable information source. Additionally, @merapi_uncover maintains user privacy by not disclosingsensitive personal information, thereby increasing public trust. It also presents visually engaging contentthat is easily understood by younger audiences. The findings suggest that @merapi_uncover'scommunication strategies are effective in enhancing public engagement and creating a citizen journalismthat serves as a bridge between the community and authorities.Keywords: Citizen Journalism, Social Media, Digital Communication.